Universal Development Goals for This Millennium - Lempert, David (Consilience, 2014)
This essay uses established United Nations treaties and agreements on human “development” and progress, that were part of the post World War II consensus, as a basis for rediscovering and reaffirming those “universal development goals” that were intended to be the measure of “development” success within all of the world’s countries and that can be recognized again as the U.N. sets its agenda and measures for post-2015 “development goals”. The author notes how the U.N.’s “Millennium Development Goals (MDGs)” established for 2001 to 2015, abandoned the earlier global consensus to substitute a narrower vision duplicating the “civilizing mission” of European colonialism. This approach undermined global aspirations and substituted a vision of homogeneity and basic needs with no possibility for progress. Current attempts to “fix” the failures of the MDGs with “Sustainable Development Goals (SDGs)” continue to subvert the earlier agreements. The 13 principles for development that the international community outlined as the basis of humanity’s development vision after World War II can serve as the basis for contemporary "Universal Development Goals.”